Neuroethics : defining the issues in theory, practice, and policy - Illes, Judy (Oxford University Press, 2006)
Recent advances in the brain sciences have dramatically improved our understanding of brain function. As we find out more and more about what makes us tick, we must stop and consider the ethical implications of this new found knowledge. This book answers many pertinent questions.